DSS for Cash Management in Indian Microfinance Institutions: A Brief Review of Literature - Singh, Ritika; Bhar, Chandan (Indian Journal of Finance, 2015)
The paper tried to identify a suitable approach to propose a Decision Support System (DSS) for cash management in MFIs. The paper reviewed microfinance literature by identifying the issues in the sector and further justifying the need for cash management DSS. Thereafter, it reviewed cash management literature by making a classification based on sub problems and approaches to mitigate it in order to identify the approach which will help managers in their day-to-day decision making. Finally, it reviewed DSS literature and classified it according to application and technique to justify the approach identified from the cash management review. The paper identified System Dynamics (SD) as the technique or approach for the future development of DSS for cash management in MFIs.